Нанокомпозиційні покриття для захисту від зношування в умовах високих температур - Shchepetov, Vitalii; Kharchenko, Sergii; Kharchenko, Olena; Dolzhenko, Gennadii (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The investigation results of friction and wear of the developed detonation composite coatings FeAl2-Ti-Si-B under high-temperature friction conditions are presented. The choice of FeAl2-Ti-Si-B composition and its optimal content for spraying wear-resistant coatings loaded with friction under high-temperature conditions are justified. It is noted that the alloying elements at definite concentrations and technological parameters of spraying have a positive influence on the structure, properties, and quality assurance of multicomponent coatings. It is shown that the introduction of silicon and boron contributes the formation of hard-alloy high-temperature compounds with increased wear resistance. The maximum microhardness corresponds to the Cr-Si coatings with ~ 28 % titan content. In addition, the mechanical properties of the obtained material are improved by additional alloying of ~ 22 % silicon and bor. In turn, the coatings plating at a working gas flow rate in a ratio for acetylene ~ (20/25) l/min and oxygen ~ (22/27) l/min provides the chemical composition and spraying process parameters permanence as well as constant properties of coatings. The obtained results show that for the coatings of FeAl2-Ti-Si-B system at loading 5.0 MPa, sliding speed 1.5 m/s, and temperature up to 650 °C the stable performance of structural adaptability, which ensures the friction and wear parameters minimization, is demonstrated. The metallographic analysis and strip chart recording of specimens indicate that the friction surfaces are characterized by the absence of visible defects; the separate cold-welded regions are located in thin-film surface layers. The composition, structure, and tribological durability of coatings produced from the elements of the country's resource base were studied; their high adhesion, physical and mechanical characteristics and wear resistance under high-temperature conditions were defined. The thin-film surface structure patterns and properties were investigated with the help of modern physical and chemical methods of analysis. It was determined that the combination of mechanical, physical, and chemical properties of the investigated coatings provides vide opportunities for their usage as effective materials under high-temperature wear conditions. According to the test results, the application of the investigated composite coatings for friction unit efficiency improvement provides their operational reliability in accordance with requirements and opportunities that appear with the development of a new competitive material for wear-resistant coatings obtained with the help of the detonation method.